tgx-12ctgx+1=0
tgx-12/tgx+1=0
tgx^2+tgx-12=0
пусть tgx=t
t^2+t-12=0
t1+t2=-1
t1*t2=-12
t1=-4 t2=3
tgx=-4 tgx=3
x=-arctg4+πn n∈z
x=arctg3+πn n∈z
Подставить ctg x=1/tg x, где tg x≠0 и домножить данное уравнение на tgx. Получим tg²x - 12 + tg x=0
tg²x + tg x-12=0
Замена tg x=t
t² + t-12=0, по т. Виета t=-4, t=3
tg x=-4, х=-arctg 4+πn, n∈Z
tg x=3, х=arctg 3 +πk, k∈z
tgx-12ctgx+1=0
tgx-12/tgx+1=0
tgx^2+tgx-12=0
пусть tgx=t
t^2+t-12=0
t1+t2=-1
t1*t2=-12
t1=-4 t2=3
tgx=-4 tgx=3
x=-arctg4+πn n∈z
x=arctg3+πn n∈z
Подставить ctg x=1/tg x, где tg x≠0 и домножить данное уравнение на tgx. Получим tg²x - 12 + tg x=0
tg²x + tg x-12=0
Замена tg x=t
t² + t-12=0, по т. Виета t=-4, t=3
tg x=-4, х=-arctg 4+πn, n∈Z
tg x=3, х=arctg 3 +πk, k∈z